(untitled) (Journal of Computational Mathematics, 1992)
An incomplete QR decomposition called QR-like decomposition is proposed and studied. The developed theory enables us to construct two new algorithms for computing multiply nonlinear eigenvalues. Several numerical tests are presented to illustrate their behavior in comparison with Kublanovskaya's approach.